Hepatitis C Virus Eradication with New Interferon‐Free Treatment Improves Metabolic Profile in Hepatitis C Virus‐Related Liver Transplant Recipients. Issue 8 (24th August 2018) - Beig, Junaid; Orr, David; Harrison, Barry; Gane, Edward
Abstract : Interferon (IFN)‐free, direct‐acting antiviral (DAA) therapy agents provide a safe and efficacious treatment for liver transplant recipients with recurrent hepatitis C virus (HCV) infection. The aim of this study is to evaluate the impact of HCV eradication on the metabolic factors in liver transplant recipients. We completed a retrospective single‐center study on HCV‐related liver transplant recipients treated with IFN‐free DAAs including both treatment‐naive and treatment‐experienced patients. IFN‐free DAAs impact on the metabolic profile were assessed at baseline and sustained virological response (SVR) between 24 and 48 weeks. In total, 91 liver transplant recipients with recurrent HCV infection received IFN‐free DAA treatment, 62 patients had IFN‐based treatment failure, and 29 were treatment‐naïve, of whom 87 (96%) achieved SVR. Eradication of recurrent HCV infection was associated with reduction in the treatment of diabetes and hypertension by 38% and 22% from the baseline respectively. Hemoglobin A1c (HbA1c) levels declined from mean 35.5 ± 4.3 mmol/mol to 33.3 ±3.6 mmol/mol at 44 weeks posttreatment ( P = 0.03). Total cholesterol levels increased from 3.8 ± 0.9 mmol/L to 4.9 ± 0.9 mmol/L at 41 weeks posttreatment ( P < 0.0001), reflecting a significant increase in serum low‐density lipoprotein (LDL) levels (2.0 ± 0.8 to 2.9 ± 0.8; P < 0.0001). Estimated glomerular filtration rate (eGFR) levels increased from 64.9 ± 20 mL/minute to 69.6 ± 20 mL/minute at 24 weeks posttreatment ( P = 0.0004). Glucose, lipid profile, and eGFR changes were independent of weight changes and immunosuppression dosage and trough levels. In conclusion, eradication of recurrent HCV infection by DAA therapy has beneficial impacts on glucose metabolism and renal profile and reverses the hypolipidemic effect of HCV in liver transplant recipients. These extrahepatic effects of DAA therapy need to be validated by larger prospective studies.